Wearable Strain Sensor Based on Double‐Layer Graphene Fabrics for Real‐Time, Continuous Acquirement of Human Pulse Signal in Daily Activities. Issue 5 (10th April 2021) - Sun, Yongzhi; Zhang, Zequn; Zhou, Yu; Liu, Shinian; Xu, Hua
Abstract: Real‐time, continuous acquirement of human pulse signal in daily activity has important clinical significance for cardiovascular disease diagnosis and healthcare system. Here, a wearable strain sensor is developed based on reduced graphene oxide (rGO) fabrics/foam tape/rGO fabrics structure to realize this goal. The wearable device is designed and fabricated with two‐layered rGO fabrics: the lower rGO fabrics that can directly attach to the skin surface acquire the superposition signal of the human daily activity and pulse, while the upper rGO fabrics can only acquire human daily activity signal because the foam substrate between the two rGO fabrics components can preclude the response of the upper rGO film to the weak pulse beat. Through comparing two signal modules, the human daily activity signal of the superposition signal can be marked and further eliminated by band‐pass filter method and the pulse signal in daily activity can be obtained. This wearable sensor displays capability to monitor human pulse signal during various daily activities, including index finger bending, middle finger bending, wrist flexion and extension, fist clenching and continuous finger flexion with different rates, thus providing a promising solution to monitor human pulse in daily activity. Abstract : Wearable strain sensor based on reduced graphene oxide (rGO) fabrics/foam tape/rGO fabrics structure is proposed and fabricated. This sensor can achieve real‐time, continuous monitoring of human pulse signal human pulse signal during various daily activities such as index finger bending, middle finger bending, wrist flexion and extension, fist clenching and continuous finger flexion with different rates.